2009 34th IEEE Photovoltaic Specialists Conference (PVSC) 2009
DOI: 10.1109/pvsc.2009.5411394
|View full text |Cite
|
Sign up to set email alerts
|

Modeling, synthesis, and characterization of thin film Copper Oxide for solar cells

Abstract: The modeling, growth, and characterization of Copper Oxide thin films for solar cell applications are reported. CU20 has several attractive properties which include its direct band gap (Eg=2.17 eV) for use in photoelectrolysis of water and use in tandem multi-junction cells. Detailed balance calculations predict efficiencies on the order of 200/0 while CU20 cells have yet to even pass 20/0 efficiency. The device physics model reveals that defects, particularly at the heterojunction interface, are the main reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Cuprous oxide (Cu 2 O) has long been studied because of the unique properties manifested in this material, including the observation of Bose–Einstein condensation of excitons. , Beyond such basic condensed matter physics studies, there has been considerable attention throughout the years given to Cu 2 O (a cubic material with a = 4.27 Å and Pn 3 m symmetry) as a candidate material for photovoltaics and photocatalysis , and even as a negative electrode material for lithium-ion batteries . What has drawn researchers to Cu 2 O for such applications are the properties: it is nontoxic, widely abundant, relatively cheap to produce, is a p-type semiconductor with a direct band gap of ∼2.1 eV, , and it has a maximum theoretical solar conversion efficiency of ∼12% in a single layer photovoltaic cell.…”
mentioning
confidence: 99%
“…Cuprous oxide (Cu 2 O) has long been studied because of the unique properties manifested in this material, including the observation of Bose–Einstein condensation of excitons. , Beyond such basic condensed matter physics studies, there has been considerable attention throughout the years given to Cu 2 O (a cubic material with a = 4.27 Å and Pn 3 m symmetry) as a candidate material for photovoltaics and photocatalysis , and even as a negative electrode material for lithium-ion batteries . What has drawn researchers to Cu 2 O for such applications are the properties: it is nontoxic, widely abundant, relatively cheap to produce, is a p-type semiconductor with a direct band gap of ∼2.1 eV, , and it has a maximum theoretical solar conversion efficiency of ∼12% in a single layer photovoltaic cell.…”
mentioning
confidence: 99%
“…Following this, the alloy is oxidized to create a predominantly copper oxide (Cu 2 O or CuO) rich surface that is self-adherent. Copper oxides have recently attracted much attention for their use as photocathodes 10 for solar water splitting, photovoltaics, 18 and as photocatalysts 19 and thus, our goal in this paper is to demonstrate viable photocathodes on brass foils. Here the brass foils act as the source substrate as well as forms a conductive electrical contact during the testing of the photocathode.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Minami et al 1) recently reported that they successfully fabricated a ZnO/Cu 2 O heterojunction solar cell with a conversion efficiency of 3.83%. Furthermore, Darvish and Atwater 2) reported that theoretical efficiencies of Cu 2 O/Si and Cu 2 O/GaAs dual junction solar cells are calculated to be 27.11 and 30.08%, respectively. Since Cu 2 O has relatively high carrier mobility of >100 cm 2 /Vs among p-type semiconductors, 3) a thin-film transistor application is also expected.…”
Section: Introductionmentioning
confidence: 99%